Recruiting a long way from home: Domino damselfish Dascyllus trimaculatus can detect new temperate coral habitat and conspecifics. Issue 6 (4th May 2022) - O'Connell, Max J.; Fowler, Ashley M.; Allan, Sam J.; Beretta, Giglia A.; Booth, David J.
Abstract: Climate change is driving tropicalisation of temperate reefs, yet it is unclear how range‐shifting tropical fishes locate suitable habitat. The authors tested whether juvenile tropical damsels Dascyllus trimaculatus could detect rare coral habitat ( Pocillopora aliciae ) and conspecifics on temperate rocky reefs using olfactory and visual preference experiments. For all cues, individuals selected and spent more time than expected in aquarium areas with the cue present, which included coral odour and conspecific odour and visual cues. This indicates that vagrant coral‐reef fish can detect rare suitable habitat outside of their natal range.